Konstruksi mitos kopi dalam representasi visual dan verbal instagram fore coffe: analisis semiotika rolland barthes - Nur Qadri Malabbi (JURNAL ILMU BUDAYA, 2026)
This study explores the construction of meaning and myth in visual and verbal representations on Fore Coffee’s Instagram account. Using a qualitative descriptive approach and Roland Barthes’ semiotic theory, posts published from March to June 2026 were analyzed through the levels of denotation, connotation, and myth. The findings reveal four major myths. First, coffee is represented as a symbol of Indonesian identity and local authenticity. Second, coffee is associated with urban mobility and modern lifestyles. Third, the portrayal of professional women during Kartini Day promotes the idea of gender equality and women’s empowerment. Fourth, Fore Coffee is depicted as a social space that accommodates personal memories and social relationships. Overall, the study demonstrates that social media plays a significant role in constructing and reproducing cultural meanings, identities, values, and collective experiences through visual and verbal representation. Keywords: semiotics, myth, representation, social media, Fore Coffee.